2019
DOI: 10.1055/s-0039-3400316
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Magnesium Sulfate Exposure and Hemodynamically Significant Patent Ductus Arteriosus in Premature Infants

Abstract: Objective  The use of antenatal magnesium sulfate (MgSO 4 ) has been associated with neuroprotective effects. One of its' proposed mechanisms of action includes antagonism of calcium channels. Calcium influx is important for closure of ductus arteriosus. We hypothesized that antenatal MgSO 4 exposure may be associated with an increased risk of hemodynamically significant patent ductus arteriosus (HsPDA) in premature infants (PI). Study Design  A prospective cohort study conducted in two parts. PI (< 32 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…However, in a study on cardiovascular effects of antenatal MgSO 4 , Paradisis et al [31] reported an incidental finding of significantly smaller PDA in the exposed group. Qasım et al [15] recently showed a decreasing trend of HsPDA with antenatal MgSO 4 exposure. In our study, antenatal MgSO 4 was associated with significantly decreased HsPDA.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in a study on cardiovascular effects of antenatal MgSO 4 , Paradisis et al [31] reported an incidental finding of significantly smaller PDA in the exposed group. Qasım et al [15] recently showed a decreasing trend of HsPDA with antenatal MgSO 4 exposure. In our study, antenatal MgSO 4 was associated with significantly decreased HsPDA.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that antenatal MgSO 4 -exposed infants had an increased risk for hypotonia, delivery room intubation, and significant patent ductus arteriosus (PDA) compared with infants not exposed to antenatal MgSO 4 [11][12][13]. However, the cardiorespiratory effect of antenatal MgSO 4 in preterm infants is still controversial [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they found that magnesium sulfate exposure did not increase the incidence of hsPDA. Based on partial statistic findings there was a significant negative correlation between antenatal MgSO4 exposure and hsPDA, they speculated that antenatal MgSO4 exposure may play a role of helping with ductal closure [36] . Besides, Elena Fridman discovered maternal aspirin treatment may be associated with a decrease likelihood of hsPDA in preterm infant and may increase infant responsiveness to postnatal medical PDAtreatment [37] .…”
Section: Clinical Markersmentioning
confidence: 99%
“…Antenatal MgSO 4 which is a calcium channel blocker may result in delayed ductal closure in infants ( 217 ). However, recent evidence in extremely low birth weight infants suggests that antenatal MgSO 4 exposure is not associated with an increased risk of hemodynamically significant PDA; in fact, it may be associated with a decreased likelihood of hemodynamically significant PDA ( 218 ). Diazoxide, which is a K ATP channel activator may induce ductal opening ( 173 ).…”
Section: Effects Of Pharmacological Agentsmentioning
confidence: 99%